Pengaruh Pemberian Olahraga Peregangan (Stretching) dan Pemberian Buah Pisang Raja (Musa Textilia) terhadap Tingkat Produktivitas Kerja Karyawan Bagian Finishing Unit Garmen - Megalestari Ratna Cendikia; Suroto Suroto; Daru Lestantyo (Jurnal Kesehatan, 2021)
One of the factors that cause a decrease in productivity is the work environment load, namely physiological factors and the capacity of workers such as work nutrition intake. Static work that is carried out with a long duration and heavy workload will cause a contractionary effect on the muscles and cause pain which will have an impact on work productivity. PT Apac Inti Corpora Semarang, especially in the garment finishing section, does ironing work in a standing position for 8 hours of work and without additional food for workers. The purpose of this study was to determine the effect of stretching and intake of bananas(Musa Textilia) toward the employee’s productivity in the garment finishing section, PT Apac Inti Corpora Semarang. This type of research is a quantitative method with a quasi-experimental design. The population in this study was 40 people and the sample was taken using the total sampling technique. The samples were divided into 4 groups, namely the intervention of stretching exercise group, intake of banana, stretching exercise and intake of bananas simultaneously, and the control group. Each group contains 10 respondents. Measurement of productivity variables uses the number of production targets for workers The results showed that there was an effect and increase in productivity (p-value=0,001) after intervening with stretching exercises and giving intake of bananas (Musa Textilia) simultaneously.